2012
DOI: 10.1016/j.solener.2012.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating shading losses in solar photovoltaic potential assessment at the municipal scale

Abstract: Recently several algorithms have been developed to calculate the solar photovoltaic (PV) potential on the basis of 2.5D raster data that can capture urban morphology. This study provides a new algorithm that (i) incorporates both terrain and near surface shadowing effects on the beam component; (ii) scales down the diffuse components of global irradiation; and (iii) utilizes free and open source GRASS and the module r.sun in modeling irradiation. This algorithm is semiautomatic and easy to upgrade or correct (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 37 publications
(63 reference statements)
0
58
0
Order By: Relevance
“…Figure 5 illustrates a visualisation of a shadow analysis. This use case is also essential in the estimation of the solar potential of buildings, which may negatively affect the photovoltaic yield of a solar panel [102,112,[222][223][224][225][226][227]. In this context, this use case is closely related to the previously mentioned one of estimating the insolation of buildings, and they are often used together.…”
Section: Estimation Of Shadows Cast By Urban Featuresmentioning
confidence: 99%
“…Figure 5 illustrates a visualisation of a shadow analysis. This use case is also essential in the estimation of the solar potential of buildings, which may negatively affect the photovoltaic yield of a solar panel [102,112,[222][223][224][225][226][227]. In this context, this use case is closely related to the previously mentioned one of estimating the insolation of buildings, and they are often used together.…”
Section: Estimation Of Shadows Cast By Urban Featuresmentioning
confidence: 99%
“…A significant relationship was found between SVF and urban heat islands at a local scale [9]. Sky obstruction can substantially reduce the amount of solar radiation reaching the ground [10], and hence SVF serves an important role in solar radiation modeling [11,12]. It was found that SVF was significantly correlated with surface emissivity in urban canyons [13].…”
Section: Introductionmentioning
confidence: 94%
“…State-of-the-art methods also consider shadowing from vegetation by either using semitransparent vegetation modelling [6] or light transmission estimation by using satellite-derived Leaf Area Index (LAI) [10]. Most of the state-of-the-art also consider only the constant efficiency of a PV module when estimating the PV potential [8]. Recently, it has been shown that it has bias in accuracy, in comparison to using the nonlinear efficiency characteristics of a PV module and a solar inverter [10].…”
Section: Introductionmentioning
confidence: 99%